Sensory and consumer evaluation of commercially available gluten-free crackers - Brar, Japneet (Kansas State University, 2024)
Celiac disease is an autoimmune disorder that causes inflammation and damage to the small intestine upon ingestion of gluten. The only effective solution for patients with celiac disease is a lifelong adherence to the complete avoidance of gluten. Gluten is a very important protein responsible for the appearance, flavor, and texture of various baked and non-baked goods. Therefore, the growing demand for gluten-free foods has prompted the food industry to develop products with better sensory properties and consumer acceptability. Crackers are important snack foods that are widely consumed and sometimes serve as an addendum to meals. Gluten-free crackers have not been studied extensively for their sensory characteristics. Therefore, this study was designed to explore sensory characteristics and consumer acceptability of gluten-free crackers. The specific objectives of this study were to 1) use an untrained consumer panel to evaluate commercially available gluten-free crackers using projective mapping for classification and development of consumer terminology using modified flash profiling. 2) to develop a lexicon using a highly trained panel to more analytically describe and characterize the specific sensory characteristics of gluten-free crackers and 3) to investigate consumer liking of gluten-free crackers with different sensory profiles. Sixteen commercial gluten-free crackers with different grain sources were initially selected. These were narrowed down to ten samples using projective mapping for further exploration. Modified flash profiling helped to characterize the different samples using extensive language, which was consumer-friendly, detailed, marketing-friendly, and easy to understand. Brown rice crackers (MAGOGF, SESGF) were described by brown rice, cardboard, and flaxseed. Their texture was described with hardness, crispiness, and grittiness. White rice (LANCGF, GLUTGF, KAMGF), tapioca/potato starch formulation (ABSOGF), and millet blend (SCHAGF) crackers were described mostly with sweet, butter and oily. Cassava flour (CRUNGF) and nut flour blend (SIMIGF) were characterized by herb, salty and savory. These samples were also evaluated by five highly trained descriptive panelists. The descriptive panel generated 43 different aroma, appearance, texture, and flavor attributes. Some of these attributes were common for all crackers such as presence/absence of holes, thickness appearance, roughness appearance, shiny, thickness, hardness, fracturability, gritty, dryness/moisture absorbency, toothstick/toothpack, astringent while some attributes were unique to certain crackers such as dairy for LANCGF, coconut for CRUNGF, seaweed and soy sauce for MAGOGF, and black pepper for SESGF. All the gluten-free crackers had high flavor intensities. This information helps understand the sensory properties of gluten-free crackers and uncover the white spaces in the market. Both the descriptive panel and consumer panel were able to achieve a clear differentiation of the samples. A central location consumer test was performed using untrained panelists who were frequent consumers of gluten-free products. Only one among the ten products evaluated received an overall mean liking of 7.0, or “like moderately”, on a 9-point hedonic scale, whereas four crackers received a mean liking score of 6.0 indicating that they were liked slightly. These results showed a huge opportunity for improvement in consumer perception of the sensory qualities of gluten-free crackers. Further research can focus on incorporating a greater number of gluten-free samples and studying the effect of different ingredients in a controlled setting on the sensory properties of gluten-free crackers.
Keywords: Gluten-free crackers; Sensory evaluation